1997
DOI: 10.1159/000291497
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Preeclampsia in Pregnancies Complicated by Fetal Malformation

Abstract: There seems to be a correlation between preeclampsia and congenital abnormalities, but whether it is positive or negative is a matter of controversy. Since it has been demonstrated that reduced perfusion of the trophoblast, which is an early feature of preeclampsia, can also represent a cause of fetal malformation, a positive correlation between the two conditions should be found. In the search for such a correlation we retrospectively examined 8,894 cases collected until 1994 by the IMER group (Indagine Malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The expression of this putative gene may be abnormal in trisomy 16, thereby predisposing to hypospadias. In a study of 8894 cases in a malformation database, an association between gestational hypertension (including preeclampsia) and the presence of malformation was found, which on multivariate analysis proved to be due specifically to hypospadias, other anomalies of the penis, and 'multiple congenital abnormalities' (syndromes affecting the face, limbs and stature) (Vesce et al, 1997). This association could be due to the presence of trisomy 16 mosaicism in a subset of the preeclampsia cases.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of this putative gene may be abnormal in trisomy 16, thereby predisposing to hypospadias. In a study of 8894 cases in a malformation database, an association between gestational hypertension (including preeclampsia) and the presence of malformation was found, which on multivariate analysis proved to be due specifically to hypospadias, other anomalies of the penis, and 'multiple congenital abnormalities' (syndromes affecting the face, limbs and stature) (Vesce et al, 1997). This association could be due to the presence of trisomy 16 mosaicism in a subset of the preeclampsia cases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when aneuploidy is present, a delayed cytotrophoblast differentiation11 and an alteration in cytotrophoblastic expression of invasion and adhesion molecules have been demonstrated12; this could explain the reduced trophoblastic invasion of the maternal vessels with persistence of unmodified spiral arteries. In addition, it has been reported that pregnancies with fetal chromosomal abnormalities13 14 and multiple fetal malformations15 are at increased risk of pre-eclampsia which, in turn, is correlated to ASAM 3…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age was modelled as a continuous variable after setting unknown maternal age ( n = 120) to the mean (age 27) and expressing age in deviations from the mean. Paternal age was modelled in categories (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and 45 + vs. others) as previously described; 14 unknowns were included with the reference category (age [25][26][27][28][29][30][31][32][33][34]. Unless otherwise stated, all models controlled for maternal and paternal ages, the three hospitals (as dichotomies, one being dummy), birth order (first vs. all others combined), maternal Rh (negative vs. positive), maternal education (unknown, 0-4, 5-12 vs. 13 + years), maternal religion (Muslim vs. non-Muslim), social class [based on husband's occupation: low (i.e.…”
Section: Data Analysis and Variablesmentioning
confidence: 99%